Teachers Readiness in Implementing the New Curriculum in Secondary Schools of Rukungiri Municipality. - Muhumuza, Christoms (Kabale University, 2024)
This study examined teachers' readiness for implementing the new curriculum in secondary schools within Rukungiri Municipality. The objectives were to assess teaching modes, resource availability, and assessment methods. A mixed-methods approach was used, combining surveys and interviews with teachers and head teachers to gather quantitative and qualitative data. Findings reveal a generally positive perception of teaching modes, with most teachers employing diverse methods and integrating technology effectively. However, there is room for improvement to ensure consistency across all classrooms. The availability of educational resources emerged as a critical issue, with significant disparities noted. While some schools have adequate materials, others face shortages, affecting the quality of teaching and learning. Assessment methods were generally perceived as effective, yet concerns about alignment with classroom topics suggest the need for better integration. The study concludes that enhancing resource provision, aligning assessments with curriculum content, and offering ongoing professional development for teachers is essential to improving the implementation of the new curriculum. Recommendations include targeted investments in educational resources, the development of professional training programs, and regular monitoring and evaluation of teaching and assessment practices. Further research is suggested on the impact of resource allocation, the effectiveness of teacher training, assessment practices, and longitudinal studies to track curriculum implementation over time.